Investigating Individual’s Energy Saving Behavior in Using Electric Vehicles: Extended Theory of Planned Behavior - Erna, Erna; Setiawan, Iwan; Aos, Aos (International Journal of Energy Economics and Policy, 2024)
The rapid climate change and its negative impacts have garnered global attention towards carbon emission mitigation efforts. The use of electric vehicles and individual energy-saving behaviors plays a crucial role in reducing carbon emissions from the transportation sector. The aim of this research is to analyze the influence of individual attitudes towards behavior, subjective norms, and perceived behavioral control on the intention and behavior of energy-saving, particularly in the context of electric vehicle usage. This study employs a quantitative approach and a survey method using a Likert-scale questionnaire. The sample of respondents consists of electric vehicle users selected through random sampling. Data was collected through questionnaires with a scale ranging from 1 to 5, and a total of 313 samples were used for analysis. Data analysis was conducted using Structural Equation Model (SEM) with the assistance of SmartPLS 4 software. The results of the analysis indicate that an individual’s attitude towards behavior plays a significant role in influencing the intention and behavior of energy-saving. Perceived behavioral control also directly influences energy-saving behavior. However, subjective norms do not have a significant impact on intention and energy-saving behavior. These findings suggest that to promote individual energy-saving behavior, there should be an emphasis on cultivating positive attitudes towards energy-saving practices and factors affecting behavioral control. This research provides valuable insights into the factors influencing individual energy-saving behavior in the context of electric vehicle usage. With a better understanding of these factors, we can contribute to global efforts to reduce carbon emissions and mitigate climate change.